Energy saving in social housing through the implementation - Guillén Guillén, César Armando (Centro Universitario de Arte, Arquitectura y Diseño, 2020)
The materials with which the social housing envelope is usually constructed in sub humid warm climate are thermally inefficient because they lead heat to interior space which affects thermal habitability. To reverse the state of thermal inefficiency of the house was introduced in the construction industry the use of thermo-insulating materials that are evaluated for their ability to resist the heat flow (Thermal Resistance), however, this adequacy in the envelope involves an additional economic cost in a context of shortage. Therefore, the objective of this research was to determine the possibility of the use of materials from the region for potential use as an insulator. Selecting the configurations of roofing materials by their coefficient of thermal conductivity and evaluating by the insulation capacity according to the nmx-c-460-onncce involving the calculation of the Thermal Resistance (R); The performance of carrizo (Arundo Donax), corn cane (Mayz Zea) and the soil was evaluating to develop a roof for the region, according to the nmx-c-460-onncce meets for energy savings. Thermal analysis of materials is discussed only for their conductivity as there are other properties such as density and specific heat, that are dynamically related, independently that are not considered in the evaluation of thermal resistance. It is concluded that the analysis of pre-design thermal properties allows to select materials with adequate thermal response in the region to build efficient architectural envelopes.